Is the Thoroughbred race-horse under chronic stress? - Nogueira, G. P. [UNESP]; Barnabe, R. C. (FapUNIFESP (SciELO), 1997)
Thoroughbred fillies were divided into three groups according to age: group 1, 7 fillies aged 1 to 2 years (G1) starting the training program; group 2, 9 fillies aged 2 to 3 years (G2) in a full training program; group 3, 8 older fillies 3 to 4 years of age (G3) training and racing. Blood samples were collected weekly from July to December. Cortisol was quantified using a solid phase DPC kit. The intra- and interassay coefficients of variation were 12.5% and 15.65% and sensitivity was 1.9 ± 0.2 nmol/ l. The semester average of cortisol levels varied between groups: G1 = 148.8 ± 6.7, G2 = 125.7 ± 5.8, G3 = 101.1 ± 5.4 nmol/l, with G3 differing statistically from the other groups. The lower cortisol levels observed in the older fillies leads us to propose that the stress stimulus, when maintained over a long period of time, may become chronic and result in a reduction of hypophyseal corticotropin-releasing hormone receptors. The secretion of endogenous opioids may also lead to low serum cortisol levels.
Keywords: Chronic stress; Cortisol; Exercise; Horses; hydrocortisone; animal; animal disease; animal experiment; blood; chronic disease; horse; horse disease; stress; Animals; Chronic Disease; Horse Diseases; Hydrocortisone; Physical Conditioning, Animal; Stress